The Association of Preoperative Medication Administration and Preoperative and Intraoperative Factors With Postoperative Urinary Retention After Urogynecologic Surgery. Issue 12 (December 2021) - Schmidt, Payton; Kobernik, Emily K.; Fairchild, Pamela S.; Anderson, Alec; Lanham, Michael; Berger, Mitchell B.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:527–531) Between 2% and 42% of women with pelvic organ prolapse (POP) or urinary incontinence experience postoperative urinary retention (PUR) within 4 weeks of surgery. PUR is managed by using urinary catheters to avoid bladder distension, but this increases the risk for urinary tract infections and patient dissatisfaction.